2000
DOI: 10.1006/game.1999.0743
|View full text |Cite
|
Sign up to set email alerts
|

Simple Mechanisms to Implement the Core of College Admissions Problems

Abstract: This paper analyzes simple mechanisms implementing (subselections of) the core correspondence of matching markets. We provide a sequential mechanism which mimics a matching procedure for many-to-one real life matching markets. We show that only core allocations should be attained when agents act strategically when faced with this mechanism. We also provide a second mechanism to implement the core correspondence in Subgame Perfect Equilibrium. Journal of Economic Literature Classification Numbers: C78, D78.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 10 publications
0
31
1
2
Order By: Relevance
“…In this context, [4] analyze Nash equilibria and showed that they coincide with the equilibria of a centralized market. 19 Other papers related to decentralized matching markets are by Peleg [9], Alcalde, Pérez-Castrillo and RomeroMedina [2], and Alcalde and Romero-Medina [3]. Their models differs from ours, however, in an important respect.…”
Section: The Literaturementioning
confidence: 81%
“…In this context, [4] analyze Nash equilibria and showed that they coincide with the equilibria of a centralized market. 19 Other papers related to decentralized matching markets are by Peleg [9], Alcalde, Pérez-Castrillo and RomeroMedina [2], and Alcalde and Romero-Medina [3]. Their models differs from ours, however, in an important respect.…”
Section: The Literaturementioning
confidence: 81%
“…On the other hand, one can also think of a mechanism in which the buyers choose simultaneously their preferred objects once the sellers have simultaneously proposed prices. This is in the spirit of the mechanisms analyzed in Alcalde, Pérez-Castrillo, and Romero-Medina (1998) and Alcalde and Romero-Medina (1999). However, in contrast with the previous papers, the implementation of the mechanism in the assignment games brings about the problem of deciding what happens if two different buyers choose the same object.…”
Section: -Conclusionmentioning
confidence: 90%
“…Alcalde, Pérez-Castrillo, and Romero-Medina (1998), and Alcalde and Romero-Medina (1999) implement through simple mechanisms the set of stable matchings in the college-admissions problem and in the job matching market, respectively. Moreover, they also implement particular subsets of the stable correspondence.…”
mentioning
confidence: 99%
“…The study of sequential matching mechanism under perfect and complete information is not new in the literature even with few examples as Alcalde et al (1998), Alcalde andRomero-Medina (2000) and(2005). Our model apparently shares features of the sequential mechanism described by Alcalde and RomeroMedina (2005).…”
Section: Introductionmentioning
confidence: 99%